Ventricular tachycardia as the first manifestation of cardiac sarcoidosis - Mehrhof, Felix (BMJ Publishing Group, 2009)
The case of a 32-year-old man with sustained ventricular tachycardia and hypotension is described. Following pharmacological treatment the patient switched to a sinus rhythm and was transferred to a university hospital for further diagnostic procedures and treatment. Cardiac catherisation ruled out underlying coronary artery disease, and cardiac MRI as well as echocardiography demonstrated a moderately reduced left ventricular ejection fraction, marked thickening of the interventricular septum and extensive intramural and epicardial infiltration of both ventricles. Endomyocardial biopsies were inconclusive; an implantable cardioverter defibrillator (ICD) was implanted in order to prevent a fatal arrhythmic event. Only repeated lymph node biopsies revealed typical findings of granulomatous disease, which together with the clinical course and the cardiac MRI findings strongly supported cardiac sarcoidosis. A few days after initiation of therapy with corticosteroids, the patient experienced the first of a number of ICD discharges, demanding aggressive anti-arrhythmic treatment regimen for the future.